Contribution of Membrane-Damaging Toxins to Bacillus Endophthalmitis Pathogenesis - Callegan, Michelle C. (American Society for Microbiology, 2002)
Membrane-damaging toxins are thought to be responsible for the explosive clinical course of Bacillus endophthalmitis. This study analyzed the contribution of phosphatidylinositol-specific phospholipase C (PI-PLC) and phosphatidylcholine-specific phospholipase C (PC-PLC) to the pathogenesis of experimental Bacillus endophthalmitis. Isogenic mutants were constructed by insertion of lacZ into Bacillus thuringiensis genes encoding PI-PLC (plcA) and PC-PLC (plcB). Rabbit eyes were injected intravitreally with 2 log(10) CFU of strain BT407 (wild type), the PI-PLC mutant (BTplcA::lacZ), or the PC-PLC mutant (BTplcB::lacZ). The rates of decrease in retinal responses of eyes infected with the isogenic mutants were similar to that of wild type, with all infections resulting in elimination of retinal function by 18 h. Strain BT407 caused a significant increase in the latency of retinal responses at 6 h, but strains BTplcA::lacZ and BTplcB::lacZ did not. All strains elicited significant inflammatory cell influx into the anterior chamber by 12 h. Histologically, eyes infected with each strain were indistinguishable throughout the infection course. In this model, neither PI-PLC nor PC-PLC had an effect on the course or severity of experimental Bacillus endophthalmitis. Alterations in retinal responses early in infection may mark the beginnings of specific photoreceptor or glial cell dysfunction.